Antimalarial primaquine for skin infiltration analgesia in rats. (1st February 2021) - Chang, Ying-Jen; Liu, Kuo-Sheng; Wang, Jhi-Joung; Chen, Yu-Wen; Hung, Ching-Hsia
Abstract: Objectives: The purpose of this study was to estimate the ability of antimalarial medications to induce local infiltration analgesia. Methods: Using a rat model of skin infiltration anaesthesia, the effects of antimalarial medications (primaquine, chloroquine, hydroxychloroquine and amodiaquine) were compared with the application of lidocaine. Key findings: At a dose of 3 μmol, primaquine and chloroquine displayed better potency (all P < 0.05) and greater duration (all P < 0.01) of cutaneous analgesia than lidocaine, whereas the other antimalarial medications showed a similar potency and duration of cutaneous analgesia when compared with lidocaine. When a dose of 3 μmol antimalarial medication was used, primaquine was the most potent and had the longest duration of action among four antimalarial medications. The relative potency ranking (ED50, 50% effective dose) has been found to be primaquine [2.10 (1.87 – 2.37) μmol] > lidocaine [6.27 (5.32 –7.39) μmol] ( P < 0.01). Infiltration analgesia of skin with primaquine had a greater duration of action than did lidocaine on the equipotent (ED25, ED50, ED75 ) basis ( P < 0.01). Conclusions: Primaquine and chloroquine have greater potency and longer lasting skin analgesia when compared with lidocaine, while the other antimalarials display a similar potency in comparison with lidocaine.